Financial management and decision making - Samuels, J. M. (John Malcolm), 1938-; Wilkes, Michael; Brayshaw, Robin (London ; Boston : International Thomson Business Press, 1999)
This book is about: The financial environment; Finance and accounting; Investment appraisal; Stock markets; ...
Keywords: Finance; Business enterprises; Corporations; Corporations -- Finance; Business enterprises -- Finance -- Case studies; Decision making